Persistent Ehrlichia ewingii Infection in Dogs after Natural Tick Infestation. (16th March 2015) - Starkey, L.A.; Barrett, A.W.; Beall, M.J.; Chandrashekar, R.; Thatcher, B.; Tyrrell, P.; Little, S.E.
Abstract : Background: Ehrlichia ewingii, which causes disease in dogs and people, is the most common Ehrlichia spp. infecting dogs in the United States, but little is known about how long E . ewingii infection persists in dogs. Hypothesis/Objectives: To evaluate the persistence of natural infection with E. ewingii in dogs. Animals: Four Class A Beagles; no previous exposure to ticks or tick‐borne infectious agents. Methods: Dogs were exposed to ticks by weekly walks through tick habitat in north central Oklahoma; dogs positive for infection with Ehrlichia spp. by sequence‐confirmed PCR and peptide‐specific serology were evaluated for 733 days (D). Whole blood was collected once weekly for PCR, and serum was collected once monthly for detection of antibodies to Ehrlichia canis (peptide p16), Ehrlichia chaffeensis (indirect fluorescence antibody [IFA] and variable‐length PCR target [VLPT]), and E. ewingii (peptide p28). Results: All dogs (4/4) became infected with Ehrlichia spp. as evidenced by seroconversion on IFA to E. chaffeensis (4/4); PCR detection of E. ewingii (4/4) and E. chaffeensis (2/4) DNA using both nested and real‐time assays; and presence of specific antibodies to E. ewingii (4/4) and E. chaffeensis (2/4). Infection with E. chaffeensis was not detected after D55. Intermittent E. ewingii rickettsemia persisted in 3 of 4 dogs for as long as 733 days. Conclusions and Clinical Importance: Our data demonstrate that dogs infected with E. ewingii from tick feeding are capable of maintaining infection with this pathogen long‐term, and may serve as a reservoir host for the maintenance of E. ewingii in nature.